Irrealis, aspect, and complementation in Old Javanese - Hunter, Thomas M (UI Scholars Hub, 2018)
This article focuses on two issues in the study of the syntax and semantics of the Old Javanese: (1) the effects of irrealis on the marking of the “passive” or Undergoer Voice verb phrases of Old Javanese, and (2) the study of complementation in Old Javanese, with particular reference to a particle n/an, first studied in an article by E.M. Uhlenbeck (1986). The study is introduced with a brief survey of some of the major components of the morphosyntactic system of Old Javanese developed largely using the analytical framework of Nicholas Himmelmann’s study (2005) of the symmetrical voice systems of the Austronesian family. Some terms like PRO have been adapted for use from more recent transformational models with a view to making the research for the paper accessible to a wider range of readers interested in syntactic and semantic issues in language.